2021
DOI: 10.3390/cancers13122979
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Clusters with Up-Regulated Expression in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignancies in Europe and North America. Early diagnosis is a key feature of efficient CRC treatment. As miRNAs can be used as CRC biomarkers, the aim of the present study was to analyse experimentally validated data on frequently up-regulated miRNA clusters in CRC tissue and investigate their members with respect to clinicopathological characteristics of patients. Based on available data, 15 up-regulated clusters, miR-106a/363, miR-106b/93/25, miR-17/92a-1, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 261 publications
0
21
0
Order By: Relevance
“…For example, the miR-106b-93-25 cluster was co-transcribed with MCM7 across all cancer types (r meta > 0.5, FDR < 0.01). The miR-106b-93-25 cluster, located in the intronic region of MCM7, is composed of highly conserved miR-106b, miR-93 and miR-25, which are upregulated in multiple cancer types [ 47 , 48 ]. It plays an important role in tumorigenesis, especially as an omco-miR in breast cancer [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the miR-106b-93-25 cluster was co-transcribed with MCM7 across all cancer types (r meta > 0.5, FDR < 0.01). The miR-106b-93-25 cluster, located in the intronic region of MCM7, is composed of highly conserved miR-106b, miR-93 and miR-25, which are upregulated in multiple cancer types [ 47 , 48 ]. It plays an important role in tumorigenesis, especially as an omco-miR in breast cancer [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs are a group of 18–24 nucleotide noncoding RNAs that bind to the 3-terminal noncoding region of the target mRNA, altering gene expression ( Sakshi et al, 2021 ; Yang et al, 2021 ) ( Figure 3 ). The aberrant expression of miRNA in tumor cells revealed that miRNAs play an essential role in tumor development by regulating the expression and function of their associated target genes and participating in a variety of physiological and pathological processes ( Barrera-Rojas et al, 2021 ; Pidikova and Herichova 2021 ; Roy et al, 2021 ). Abundant miRNAs have been proved to regulate tumor metabolism and function as an essential role in the process of glycolysis in OC ( Table 1 ).…”
Section: The Regulatory Mechanism Of Ncrnas In the Glycolysis Of Ovar...mentioning
confidence: 99%
“…In a different context, lncRNA AGER-1 induced cell cycle arrest and promoted apoptosis, thereby inhibiting cell proliferation and migration efficiency of tumor cells in several types of cancer [ 105 ]. Yet another study indicated the sponging effect of lncRNA AGER-1 for miR-182, an inhibitor of AGER1 [ 106 ]. Recently, a study showed that both AGER and its positive regulator lncRNA AGER-1 have the significant diagnostic potential for lung adenocarcinoma.…”
Section: Understanding the Role Of Lncrnas In Ages-related Dnmentioning
confidence: 99%